Evaluation of Intrinsic Motivation of Nursing Students Based on Perceived Motivational Climate - Saiideh Norouzi; Farhad Ramezanibadr; Ali Norouzi (Zanjan University of Medical Sciences and Health Services, 2018)
Background and Objective: The study aimed to determine the intrinsic motivation of undergraduate nursing students based on their perceived motivational climate. Materials and Methods: This cross-sectional research was conducted on 165 students, who were selected through simple random sampling. Data collection tools were standard intrinsic motivation and perceived motivational climate (consisting of perceived mastery and performance climates) questionnaires. Moreover, data analysis was performed in SPSS using Pearson's correlation coefficient, analysis of variance, and linear regression. Results: In this research, a significant and positive relationship was observed between intrinsic motivation and perceived mastery and motivational climates (P<0.01). In addition, a significant and positive correlation was found among the perceived mastery, performance and motivational climates (P<0.01). Results of the linear regression demonstrated that the perceived mastery and motivational climates predicted the intrinsic motivation of students while the perceived performance climate failed to do so. Conclusion: According to the results of the study, it seems that improvement and modification of the perceived mastery and motivational climates in learning environments can increase intrinsic motivation for learning in students.